Об одном особом типе предложения в системе сложноподчиненных предложений русского языка - Тинь, Нгуен Хыу; Зиап, Ву Динь (VNU Journal of Foreign Studies, 2009)
This paper analyses the structural and semantic characteristics of fixed phrases which serve as bases for the formation of complex sentences with temporal subordinate components linked with one another in a phrasal way - a type of sentences that has not been thoroughly studied in the system of Russian complex sentences. The paper also points out issues to be further considered when conducting research on the syntaxes of Russian complex sentences. It is hoped that this paper will make a modest contribution to Russian research as well as teaching Russian as a foreign language and provide useful suggestions for final-year and graduate students of Russian when they select research orientations and topics.